Moda y mujer en café, con aroma de mujer y yo soy betty, la fea : una historia de la moda y género en las representaciones femeninas colombianas de los años 90 (2020)
Fashion as an object of social study has not really been of interest to historians around the world. When trying to make a historiographical balance on fashion, it can be understood that until now the history of fashion has been a task of different authors from the social sciences and humanities, who, from sociology, anthropology, philosophy, the history of art and social communication, have created discourses on fashion through time and space. Although it is true that the history of fashion has not been made by the historical discipline, the other disciplines have approached the phenomenon from the categories of analysis used in it. This research seeks to make a history of fashion in the most representative Colombian telenovelas of the 90s: Café, con aroma de mujer and Yo soy Betty, la fea. In addition, it proposes the telenovela as a primary source to study fashion and the history of gender in Colombia, from categories such as class and identity.